Rotary equipment vibration analysis based on phase trajectories - A. V. Tsurko; A. P. Aslamov; Y. P. Aslamov; I. G. Davydov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The article introduces method of vibration signals representation based on phase trajectories. The method is proposed as a supplement for current methods in expert systems of vibration analysis to solve tasks of prior uncertainty. Preliminary feasibility analysis of the method was carried out by visual comparison using large data selection.